Design and Experiment of Greenhouse Self-Balancing Mobile Robot Based on PR Joint Sensor - Yaohui Zhang; Yugang Song; Fanggang Lu; Dongxing Zhang; Li Yang; Tao Cui; Xiantao He; Kailiang Zhang (Agriculture, 2023)
To avoid issues such as the greenhouse working robot’s inability to perform normal tasks or reduced working accuracy due to the influence of uneven ground, this study designed a set of greenhouse self-balancing mobile robots. The self-balancing mobile robot system designed in this study uses a quadruped mobile robot as a carrier, equipped with a three-degrees-of-freedom wheel-leg structure and is complemented with a posture control algorithm. The algorithm calculates the adjustment of each leg based on the vehicle’s tilt angle and wheel-ground pressure, achieving control over the robot’s posture angle, the center of gravity height, wheel-ground contact force, and other functions. To address the issue of over-constrained (weak legs) posture adjustment during mobile robot fieldwork, a flexible joint sensor based on the PR structure has been designed and developed. After field testing, it was verified that the greenhouse self-balancing mobile robot proposed in this study can adapt well to field environments, such as climbing hills, overcoming obstacles, crossing furrows, and so on. The response speed of the flexible joint sensor can meet the requirements of self-balancing while effectively solving the problem of weak legs.